Prenatal diagnosis and postnatal verification in fetuses with total anomalous pulmonary venous connection - Xue, Xiaoying; Wu, Qiumei; Xiong, Mingtao; Ling, Wen; Guo, Shan; Ma, Hong; Huang, Biying; Liu, Min; Qiu, Xiuqing; Weng, Zongjie (Frontiers in Pediatrics, 2023)
Objective To systematically verify the accuracy of a four-step prenatal ultrasonography in diagnosing fetal total anomalous pulmonary venous connection (TAPVC). Methods A total of 62 TAPVC fetuses received prenatal ultrasonography and were confirmed by postnatal echocardiography, surgery, or postabortion autopsy. The suspected TAPVC fetuses were further screened by a four-step prenatal ultrasonography for TAPVC classification, pulmonary venous obstruction, and the associated malformations, and followed postpartum. The sonographic features, clinical data, and prognosis of the TAPVC fetuses were retrospectively analyzed. Results Of the 62 TAPVC fetuses, supracardiac TAPVC was found in 20 cases, intracardiac TAPVC in 12, infracardiac TAPVC in 21, and mixed TAPVC in 9. A total of 30 cases with right atrium isomerism were correctly diagnosed. Of the 11 cases with other intracardiac and extracardiac malformations, 1 case was missed to be diagnosed. Of the 21 isolated TAPVC cases, 6 were missed prenatally and 1 case was prenatally diagnosed as intracardiac and postnatally proved to be mixed (intracardiac type + supracardiac type) by echocardiography. Of the 13 TAPVC live births, 4 infants died in the neonatal period without operation. Of the nine infants undergoing the operation, five recuperated and survived; one survived but had complications with superior vena cava obstruction and collateral circulation formation, and three died postoperatively. Conclusion The four-step prenatal ultrasound procedure can comprehensively and systematically evaluate fetal TAPVC, detailing the classification, potential obstruction, and associated malformations. It provides substantial support for subsequent prenatal counseling and neonatal assessment. The retrospective analysis also reveals that isolated TAPVC is more prone to be missed in diagnosis.